Entangling Schrödinger’s cat states by bridging discrete- and continuous-variable encoding - Daisuke Hoshi; Toshiaki Nagase; Sangil Kwon; Daisuke Iyama; Takahiko Kamiya; Shiori Fujii; Hiroto Mukai; Shahnawaz Ahmed; Anton Frisk Kockum; Shohei Watabe; Fumiki Yoshihara; Jaw-Shen Tsai (Nature Communications)
Abstract In quantum information processing, two primary research directions have emerged: one based on discrete variables (DV) and the other on the structure of quantum states in a continuous-variable (CV) space. Integrating these two approaches could unlock new potentials, overcoming their respective limitations. Here, we show that such a DV–CV hybrid approach, applied to superconducting Kerr parametric oscillators (KPOs), enables us to entangle a pair of Schrödinger’s cat states by two methods. The first involves the entanglement-preserving conversion between Bell states in the Fock-state basis (DV encoding) and those in the cat-state basis (CV encoding). The second method implements a $$\sqrt{{{{\rm{iSWAP}}}}}$$ iSWAP gate between two cat states following the procedure for Fock-state encoding. This simple and fast gate operation completes a universal quantum gate set in a KPO system. Our work offers powerful applications of DV–CV hybridization and marks a first step toward developing a multi-qubit platform based on planar KPO systems.